Knowledge Management Success Factors for Indonesia Local Government: Case Study Pontianak City Government - Irni Irmayani; Sabrina Editha Putri; Dana Indra Sensuse; Sofian Lusa; Nadya Safitri; Damayanti Elisabeth (Green Publisher Indonesia, 2025)
In Indonesia's e-Government, knowledge management is one of mandatory indicators that must be implemented at both the central and local government levels. Unfortunately, the use of knowledge management in Indonesia's local government is still very lacking. This condition is reflected in the e-government management index score at the city level nationally in 2024, which only reached 2.03, categorized as sufficient. However, knowledge management is a crucial foundation for the development of public services and innovation in local government. The aim of this study is to identify the Critical Success Factors (CSF) for the implementation of knowledge management in the Pontianak City Government through survey and interview methods. Data analysis was conducted using Structural Equation Modeling-Partial Least Square, with knowledge management as the latent variable. The results of the study suggest that innovation, measurement, regulation and technology adoption have a significant positive impact on knowledge management implementation strategies in local government. Thes success factors are the used as guidelines for developing knowledge management strategies in the Pontianak City Government, and local government in general.